Phytoremediation potential of some grasses on lead heavy metal in tailing planting media of former tin mining - NYAYU SITI KHODIJAH; RUJITO AGUS SUWIGNYO; M UMAR HARUN; LUCY ROBIARTINI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Khodijah NS, Suwignyo RA, Harun MU, Robiartini L. 2019. Phytoremediation potential of some grasses on lead heavy metal in tailing planting media of former tin mining. Biodiversitas 20: 1973-1982. Agricultural production on tin tailings land must consider the safety of products from Pb metal contaminants. The presence of Pb metal can be overcome by using plants as phytoremediation. This study aimed to obtain information on the ability of phytoremediation of Pb by various types of grass and its interaction with the types of ameliorants in tin tailings media. Three species of grass were used, namely Pennisetum purpureum, Saccharum spontaneum, and Hymenachne acutigluma, and two types of ameliorant, namely lime and compost. The study was designed using a factorial treatment design laid out in a completely randomized design with two treatment factors, namely the type of grass and the type of ameliorant. Observations were done on growth, shoot Pb content and root Pb content. The ability of phytoremediation was assessed by using the approach of Bioconcentration factor (BCF) and Translocation Factor (TF) values. The highest phytoremediation ability was found in treatment of H. acutigluma grass treated with lime ameliorant, followed by S. spontaneum treated with lime ameliorous and S. spontaneum treated with compost ameliorant. Based on BCF values, P. purpureum and H. acutigluma were categorized as accumulators, and S. spontaneum was classified as an excluder. Based on TF values, the three types of grass used were classified as phytostabilisation. The high ability of phytoremediation in H. acutigluma was caused by its high BCF values, ??while the high ability of phytoremediation on S. spontaneum was caused by its low translocation factor value and high Pb absorption efficiency.